Decisions and involvement of cancer patient survivors: a moral imperative - Pravettoni G; Cutica I; Righetti S; Mazzocco K (Dove Medical Press, 2016)
Gabriella Pravettoni,1,2 Ilaria Cutica,1,2 Simona Righetti,1 Ketti Mazzocco1,2 1Department of Oncology and Hematology, University of Milan, 2Applied Research Division for Cognitive and Psychological Science, European Institute of Oncology, Milan, Italy Purpose: The aim of this study was to review the experiences of direct involvement in patient survivorship for treatment and research. Methods: This is a narrative-focused review of the following two recent experiences of patient involvement: the Chordoma Foundation and the Triple Negative Breast Cancer Foundation. Results: These two examples represent concrete experiences that patients have built to favor a real involvement in the care and treatment of tumors. These experiences are profoundly modifying how cancer research is conducted and draw attention to the psychosocial dimensions of health care. Conclusion: These examples represent the new scenario in which modern medicine faces completely new challenges, copes with new needs, and cooperates with new health care professionals. Implications: Involving patients in a new perspective raises practical and ethical challenges for organizations to work together, for health providers to be professionally skilled and for the government to promote safeguarding policies. Keywords: patient empowerment, patients’ association, empowerment, skills, codesign techniques, cancer